Petrogenesis and geodynamic implication of the newly recorded Cryogenian Suwaj adakitic magmatism at the eastern Arabian-Shield - Mahmoud M. Hassan; Osama K. Dessouky; Abdullah M. Al Shammari; Adeeb N. Al Barakati; Saad M. Al Garni; Mubark M. Al Nahdi; Ashraf N. Al Qubsani; Wadee A. AlKashghari; Sobhi Nasir; Kamal A. Ali; Mahrous Abu El-Enen (Scientific Reports)
Abstract Recent reconnaissance geochemical investigations have unveiled Cryogenian magmatism linked to the compressional accretionary phase, contributing to the growth of the Afif Terrane in the eastern Arabian Shield. The Cryogenian Suwaj intrusive suite, within the Afif Terrane, displays a compositional range from gabbro-diorite to tonalite-granodiorite. The uniform compositional variation is primarily due to magmatic differentiation within parental magma across multiple pulses. The I-type calc-alkaline Suwaj granitoids represent arc-related juvenile materials resulting from the partial melting of a metabasaltic source. The geochemical characteristics of the Suwaj granitoids suggest typical adakite formation resulting from the melting of the basaltic portion of the young, hot oceanic slab. The age correlation between the Halaban ophiolite and the Suwaj Suite aligns with adakite formation in convergent margins. Tectonically, the Suwaj suite’s origin is attributed to the subduction of the Paleo-Ad-Dawadmi oceanic slab during microplate amalgamation, reflecting an integral part of the Arabian-Nubian Shield’s evolution, underscoring crustal thickening after arc collision.